The Marginal Value of Cash: Structural Estimates from a Model with Financing and Agency Frictions - Dasgupta, Sudipto; Li, Di; Li, Erica X. N. (Management Science, 2025)
How much value does an additional dollar of cash create for a firm? It is generally recognized that the marginal value of cash (MVC) can either exceed or fall below one dollar. Estimates of MVC can guide corporate cash and payout policy, indicate the quality of governance, and make a firm a target for takeover or activism. Yet the existing methods of estimation lack a rigorous theoretical foundation and often provide implausibly high or low estimates. In this paper, we provide a formulation of MVC and structurally estimate the MVC based on a model that encompasses the important determinants for the choice of cash savings, including financing and agency costs. We find that firms with large cash and capital stocks have lower marginal value of cash, whereas the relationship between leverage and marginal value of cash is hump shaped. Two quasi-natural experiments validate the MVC estimates. This paper was accepted by Lukas Schmid, finance. Funding: D. Li would like to thank the support by the Guangdong Natural Science Foundation [Grant 2024A1515011703]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01013 .